2021
DOI: 10.1101/2021.10.14.21264933
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential features of the fifth wave of COVID-19 associated with vaccination and the Delta variant in a reference hospital in Catalonia, Spain

Abstract: Since the beginning of the COVID-19 pandemic, Spain has suffered five waves of infection, the latter being related to the expansion of the Delta variant and with a high incidence. A vaccination campaign began in December 2020 and by the end of the fifth wave 77.3% of people had been fully vaccinated. Understanding the impact of these new characteristics on COVID-19 is essential for public health strategies. Our objective was to ascertain any differences in the characteristics and outcomes of hospitalized patie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…It has been widely reported that vaccines against COVID-19 had greatly contributed to reducing the number of severe disease and therefore hospitalizations and mortality [2,3] but have failed in preventing the spread of the SARS-CoV-2 variants. However, the lack of correlation between the epidemiological variables of COVID-19 and vaccine coverage in France is certainly attributed to the combination of several factors, such as the gradual decline of vaccine efficacy [4,5,6,7]; lower vaccine's effectiveness against highly infectious spread of new SARS-CoV-2 variants, as well as the improvement of medical care for COVID-19 patients, and probably a fairly significant development of natural immunity.…”
Section: Conclusion and Proposalmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been widely reported that vaccines against COVID-19 had greatly contributed to reducing the number of severe disease and therefore hospitalizations and mortality [2,3] but have failed in preventing the spread of the SARS-CoV-2 variants. However, the lack of correlation between the epidemiological variables of COVID-19 and vaccine coverage in France is certainly attributed to the combination of several factors, such as the gradual decline of vaccine efficacy [4,5,6,7]; lower vaccine's effectiveness against highly infectious spread of new SARS-CoV-2 variants, as well as the improvement of medical care for COVID-19 patients, and probably a fairly significant development of natural immunity.…”
Section: Conclusion and Proposalmentioning
confidence: 99%
“…Analysis of Variance of Mortality, Hospitalization, and Incidence Ratios vs. Two Doses Vaccine Mean RateOn the other hand, the least vaccinated territories have experienced a decreasing regression of the variables of the COVID-19 epidemic in relation to the vaccination rates. Even though such relationship is weak or moderate (0.35 < R2 …”
mentioning
confidence: 99%
“…In the world, a massive part of the population has been infected by SARS-CoV 2 irrespective of age and gender [8]. At the beginning of 2022, several countries, like China and Spain, faced the fth wave of COVID-19 despite taking two doses of vaccination [9,10].…”
Section: Introductionmentioning
confidence: 99%